Ependymomas with extraneural metastasis to lung in children: A case report and literature review - Ge, Shunnan; Lou, Miao; Zhang, Jiarui; Chao, Min; Jiao, Yang; Gao, Guodong; Qu, Yan; Wang, Liang (Archives of Case Reports, 2020)
Ependymomas, which account for 10% of pediatric central nervous system (CNS) tumors, arise from the ependymal cells that line the cerebral ventricles and the central canal of the spinal cord. Extraneural metastasis to lung is rare for ependymomas primary tumors. Repeated surgeries that disrupt the blood-brain barrier may contribute to haematogenous spread, but the mechanism remains unclear. We present a case of ependymoma with extraneural metastasis to lung in a child and discuss reported cases of extracranial metastatic ependymoma with this presentation.